Analisis perbandingan risiko imbal hasil bank umum syariah ‎di Indonesia pada saat pandemi Covid-19 dan pasca pandemi ‎Covid-19‎ - Ahmad, Yusuf Falaqi; Kurniawan, Ahmad Rofiyudin (Maliki Interdisciplinary Journal, 2023)
This research discusses the management of risk-return trade-offs in Islamic banking in Indonesia during and after the Covid-19 pandemic. The growth of Covid-19 has impacted the economy and banking sector in Indonesia, including Islamic banks. Risks such as non-performing financing, liquidity, and market risks have been felt by Islamic banks. These risks can affect the performance, profitability, and intermediation role of Islamic banking institutions. This study uses a quantitative method with descriptive analysis. Secondary data on Islamic banking were obtained from the Financial Services Authority (OJK) during and after the Covid-19 pandemic. The t-paired sample test was used to compare the risk-return trade-offs before and after the pandemic. The results of the analysis show that there are differences in the risk-return trade-offs between the pandemic and post-pandemic periods. The average risk-return trade-off increased from 46.6517 to 49.0433 after the pandemic. This indicates that the management of Islamic banking has successfully managed the risk-return trade-offs well during the pandemic. Risk management in Islamic banking involves the identification, evaluation, measurement, and management of risks. Risk-return trade-offs in Islamic banking need to be controlled through effective risk management. The Covid-19 pandemic and changes in customer behavior are factors that influence expectations regarding returns, but Islamic banking management has successfully limited those expectations, as indicated by the increase in the risk-return trade-offs. In conclusion, this research shows that the risk-return tradeoffs of Islamic banking in Indonesia increased after the Covid-19 pandemic. The risk management of Islamic banking successfully addressed the risk-return trade-offs during the pandemic. This study provides an understanding of risk-return trade-offs management in the context of Islamic banking and insights for practitioners and decision-makers in the Islamic banking sector.